2008
DOI: 10.1007/s10800-008-9659-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of MnO2-incorporated high performance aluminum alloy matrix sacrificial anodes

Abstract: Manganese dioxide, a potential catalyst in many electrochemical reactions, was explored as an effective activator in Al ? 5% Zn alloy sacrificial anodes. The catalytic influence of MnO 2 on the anodes was microstructurally and electrochemically characterized using different electrochemical techniques. The process of incorporation of MnO 2 not only improved the grain size but also the galvanic performance of the anodes significantly. A galvanic performance as high as 80% was achieved by incorporating an optimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…These findings can be interpreted in the light of interaction thermodynamics between molten aluminum matrix and incorporated oxides, thermodynamic stability of alumina is much higher than that of manganese dioxide which has led to an in-situ metallothermic reduction by aluminum during master alloy processing and master alloy dilution that gave free dissolved manganese in the matrix [39][40]. This result is contradicting with the findings of Shibli et al that showed MnO2 has been incorporated into the matrix without validating nature of inclusion using available characterization techniques [13]. However, the situation is way more different for silica which cannot be easily reduced by aluminum as it needs a temperature of around 1200 o C and holding time of 30-120 minutes to complete the reduction [41], these conditions of Figure 9.…”
Section: Iiiiii Scanning Electron Microscope Analysismentioning
confidence: 86%
See 1 more Smart Citation
“…These findings can be interpreted in the light of interaction thermodynamics between molten aluminum matrix and incorporated oxides, thermodynamic stability of alumina is much higher than that of manganese dioxide which has led to an in-situ metallothermic reduction by aluminum during master alloy processing and master alloy dilution that gave free dissolved manganese in the matrix [39][40]. This result is contradicting with the findings of Shibli et al that showed MnO2 has been incorporated into the matrix without validating nature of inclusion using available characterization techniques [13]. However, the situation is way more different for silica which cannot be easily reduced by aluminum as it needs a temperature of around 1200 o C and holding time of 30-120 minutes to complete the reduction [41], these conditions of Figure 9.…”
Section: Iiiiii Scanning Electron Microscope Analysismentioning
confidence: 86%
“…The reinforcements added to AMMC's to boost their mechanical properties are, and not limited to, SiC ,B4C, BN, TiC, TiB2 , ZrO2, Al2O3, graphite and carbon nanotubes [5][6][7][8]. However, advantages of AMMC's have not been restricted to enhancement of mechanical properties, Shibli et al showed that incorporation of metal-oxides into Al-Zn alloys showed an improvement in its electrochemical properties when used as sacrificial anodes for cathodic protection purposes, several metal-oxides have been implemented for this target like IrO2, CeO2, RuO2, ZnO, Al2O3 and MnO2 [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Test of (Al-4% Zn-0.2% Sn)Alloy: Fig. (8) Shows the polarization data of the sacrificial anode (Al-4% Zn-0.2% Sn) alloy. The polarization curve shows that the i corr of alloy is equal to (6.15µA/cm²).…”
Section: Tafel Extrapolationmentioning
confidence: 99%
“…Aluminum is the most commonly used sacrificial material for cathodic protection of steel in sea water [8]. The usefulness of pure aluminum as an anode material in seawater is reduced significantly by the formation of a protective oxide film, which limits both its current and potential output.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of nano metal oxides and composites synergistically and significantly improves the metallurgical characteristics of anodes [4,11,12]. Recently catalytic activity of Ni nanoparticle has gained significance in many fields.…”
mentioning
confidence: 99%